Self-cleaning nano coating material and preparation process thereof
By adopting multifunctional composite materials and multi-layer structural design in the self-cleaning coating, combined with specific preparation processes, the coating is solved in terms of mechanical strength, photocatalytic performance, repair ability and environmental adaptability, and the effects of high mechanical strength, wide spectrum photocatalytic, self-healing and long-term stability are achieved.
Patent Information
- Application Number
- CN202411790914.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-25
AI Technical Summary
The existing self-cleaning coatings have shortcomings in mechanical strength, photocatalytic performance, repair ability and environmental adaptability, resulting in poor performance in complex application scenarios and environments.
The multifunctional composite material design is adopted, and the mechanical strength, photocatalytic properties, self-healing ability and chemical stability of the coating are improved through the combination of nanosilicon dioxide, nanoalumina, graphene nanosheets, nitrogen-doped titanium dioxide, fluoride silane and microcapsule repair systems, combining multi-layer coating structure and specific preparation processes.
It significantly improves the mechanical strength and durability of the coating, achieves wide spectrum photocatalytic performance, has self-healing function, and maintains long-term stability and superhydrophobic performance in harsh environments.
Smart Images

Figure CN119684883A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional nanomaterials, in particular to a self-cleaning nano coating material and a preparation process thereof. Background Art
[0002] As a functional material, self-cleaning nano coatings are widely used in architectural glass, solar panels, automotive surfaces, and high-end electronic equipment housings. They achieve functions such as stain degradation, waterproofing, and anti-fingerprinting through the photocatalytic or super-hydrophobic properties of the surface. The self-cleaning coatings in the prior art mainly rely on a simple combination of a single layer of nanomaterials and functional polymers, which achieves a self-cleaning effect to a certain extent. However, with the complexity of application scenarios and the extension of the use cycle, the technical bottlenecks of existing self-cleaning coatings are gradually exposed, mainly manifested in the following aspects:
[0003] Insufficient mechanical strength of coating
[0004] Existing self-cleaning coatings usually use single nanoparticles (such as titanium dioxide, silicon dioxide) or functional polymer materials. The mechanical properties of such coatings rely on the characteristics of the material itself and lack a systematic composite reinforcement design. Nanoparticles have poor dispersion in the coating and are prone to agglomeration, resulting in a loose coating structure and poor scratch and friction resistance. After long-term use or external impact, the coating is prone to peeling or failure, limiting its performance in application scenarios with high mechanical stress, such as automotive glass or industrial equipment surfaces.
[0005] Photocatalytic coatings rely on UV light, so performance is limited in low-light conditions
[0006] Traditional photocatalytic coatings mainly use pure titanium dioxide (TiO2) as a photocatalyst. Although it shows high catalytic efficiency in the ultraviolet light band, its absorption capacity in the visible light band is low due to its large bandgap (3.2eV). Under weak light conditions (such as indoor light or cloudy environment), the degradation efficiency of the photocatalytic coating is significantly reduced, and it is difficult to continuously perform the self-cleaning function. This limitation significantly limits the scope of application of the photocatalytic coating.
[0007] Damaged coating cannot be repaired
[0008] The functionality of self-cleaning coatings usually depends on the surface micro-nanostructure or chemical functional groups. Once the coating is scratched or partially worn, these micro-nanostructures or functional groups will be destroyed, causing the self-cleaning ability of the coating to decline rapidly. Currently, most coatings lack self-repair mechanisms and cannot automatically restore their functions after being damaged. They have a short service life and need to be repaired manually or replaced as a whole, which increases maintenance costs.
[0009] Superhydrophobic coatings are unstable in complex environments
[0010] Existing super-hydrophobic coatings are usually prepared with low surface energy materials (such as fluorinated silane) and combined with micro-nano structures to form super-hydrophobic surfaces. However, such coatings have poor chemical stability under ultraviolet aging, hot and humid environments, or acid-base corrosion conditions, and their hydrophobic properties are easily reduced; at the same time, the micro-nano structures are easily damaged by mechanical friction or impact, resulting in the failure of the super-hydrophobic function of the coating. This problem of poor environmental adaptability limits the widespread application of coatings in outdoor or industrial environments.
[0011] Therefore, the present invention proposes a self-cleaning nano coating material and a preparation process thereof to solve the deficiencies of the prior art. Summary of the invention
[0012] In view of the problems of insufficient mechanical strength, dependence of photocatalytic performance on ultraviolet light, inability to repair after damage, and unstable performance in complex environments in the prior art self-cleaning coating, the present invention provides a self-cleaning nano coating material and its preparation process. Through the combination of multifunctional composite material design, multi-layer coating structure optimization and composite preparation process, the mechanical properties of the coating are enhanced, the photocatalytic wide spectrum response is improved, the self-repair ability is improved, and the long-term stability is significantly improved.
[0013] To achieve the above objectives, the present invention is implemented by the following technical scheme: The self-cleaning nano coating material comprises the following components, calculated by weight percentage:
[0014] Nano silicon dioxide: 10%-15%,
[0015] Nano-alumina: 5%-8%,
[0016] Graphene nanosheets: 1%-3%,
[0017] Nitrogen-doped titanium dioxide: 8%-12%,
[0018] Fluorinated silane: 2%-5%,
[0019] Polyurethane: 30%-40%,
[0020] Polydimethylsiloxane: 10%-15%,
[0021] Microcapsule repair system: 3%-6%,
[0022] Ethanol: 20%-30%,
[0023] Deionized water: 5%-10%.
[0024] Preferably, the nitrogen-doped titanium dioxide is subjected to nitrogen doping treatment at 400-500° C., specifically comprising the following steps:
[0025] (1) mixing a titanium dioxide precursor and urea in a molar ratio of 1:2, wherein the titanium dioxide precursor is tetrabutyl titanate;
[0026] (2) adding deionized water, adjusting the pH value of the solution to 4-5, and stirring to form a uniform solution;
[0027] (3) subjecting the mixed solution to a hydrothermal reaction at 180° C. to 200° C. for 10 to 12 hours to obtain a nitrogen-doped titanium dioxide primary product;
[0028] (4) The primary product is placed in a nitrogen atmosphere and calcined at 400-500° C. for 2 hours to obtain nitrogen-doped titanium dioxide with a wide spectrum response capability.
[0029] Preferably, the nano silicon dioxide and nano aluminum oxide in the reinforcing material are treated with a silane coupling agent KH-550 so that the particle surface has silicon oxygen functional groups, which specifically includes the following steps:
[0030] (1) mixing nano-silicon dioxide and nano-aluminum oxide in a weight ratio of 2:1 and adding the mixture to a mixed solution of ethanol and deionized water;
[0031] (2) adding KH-550 silane coupling agent to the solution, the amount of which is 2%-3% of the total weight of the particles;
[0032] (3) stirring the mixture at room temperature for 50-60 minutes to allow the silane coupling agent to chemically adsorb on the surface of the particles;
[0033] (4) After ultrasonic dispersion for 20-30 minutes, the mixture was washed with deionized water for three times, centrifuged, and finally dried at 60° C.-70° C. for 12 hours to obtain surface-modified nano-silicon dioxide and nano-aluminum oxide particles.
[0034] Preferably, the preparation process of the self-cleaning nano coating material is characterized by comprising the following steps:
[0035] Substrate surface pretreatment: Place the substrate in a solution of isopropanol and deionized water in a volume ratio of 1:1, ultrasonically clean for 10 minutes, rinse with deionized water and dry at 60°C for 20 minutes; etch the substrate surface with 50W oxygen plasma for 5 minutes;
[0036] Enhanced particle surface modification: 15%-20% of the total weight of nano-silicon dioxide and nano-alumina are added to 100 mL of ethanol solution, and 2% of the total weight of the particles is added with silane coupling agent KH-550. After stirring for 60 minutes, ultrasonic dispersion is performed for 30 minutes, and then centrifugal separation and drying are performed to obtain modified particles.
[0037] Dissolving the matrix material: dissolving polyurethane and polydimethylsiloxane in a mixed solution of ethanol and deionized water respectively, stirring for 60 minutes to form a uniform matrix solution;
[0038] Introduction of functional additives: nitrogen-doped titanium dioxide and fluorinated silane were added to the matrix solution in proportion to the total weight of the coating, stirred for 30 minutes and ultrasonically dispersed for 10 minutes;
[0039] Composite coating mixing: Add the modified particles and microcapsule repair system into the base solution and perform ultrasonic dispersion for 30 minutes to form a uniform coating;
[0040] Multi-layer coating preparation:
[0041] The bottom layer material is coated on the surface of the substrate by chemical vapor deposition technology with a thickness of 2-5 μm and cured at 120°C for 30 minutes;
[0042] The intermediate layer material is coated on the bottom surface by spin coating technology at a rotation speed of 1000 rpm, with a thickness of 5-10 μm, and cured at 80° C.-100° C. for 10-20 minutes;
[0043] The surface material is coated on the surface of the middle layer by spraying technology with a thickness of 1-3 μm, and cured by ultraviolet light with a wavelength of 365 nm for 10 minutes;
[0044] Post-treatment: Use isocyanate treatment to enhance the interlayer bonding strength, and heat treat at 150℃-200℃ for 8-15 minutes.
[0045] Preferably, the microcapsule repair system is composed of epoxy resin as a repair agent and urea-formaldehyde resin as a capsule wall material, and the particle size of the microcapsules is in the range of 2-5 μm.
[0046] Preferably, the bottom layer comprises a composite coating of nano-silicon dioxide, nano-aluminum oxide and graphene nanosheets, which specifically comprises the following steps:
[0047] (1) mixing nano-silicon dioxide, nano-aluminum oxide and graphene nanosheets in a weight ratio of 6:3:1, adding the mixture to ethanol, and dispersing the mixture by ultrasonic for 60 minutes to form a uniform dispersion;
[0048] (2) coating the dispersion on the surface of the substrate by chemical vapor deposition technology, adjusting the vapor pressure to 20-30 Pa and the reaction temperature to 300-400° C.;
[0049] (3) The coating thickness is adjusted to 2-5 μm and cured at 120° C.-140° C. for 20-30 minutes to form a base structure.
[0050] Preferably, the intermediate layer comprises a composite solution of polyurethane and polydimethylsiloxane, and specifically comprises the following steps:
[0051] (1) adding polyurethane and polydimethylsiloxane in a weight ratio of 3:1 into a mixed solution of ethanol and deionized water;
[0052] (2) while stirring the solution to make it uniform, adding 0.5% to 1% by weight of a crosslinking agent, and continuing to stir for 60 minutes;
[0053] (3) using a spin coating technique, coating the solution on the surface of the bottom layer at a rotation speed of 1000 rpm to form an intermediate layer with a thickness of 5-10 μm;
[0054] (4) The coated intermediate layer is placed at 80°C-100°C for curing for 10-20 minutes.
[0055] Preferably, the surface layer comprises a composite coating of nitrogen-doped titanium dioxide and fluorinated silane, which specifically comprises the following steps:
[0056] (1) adding nitrogen-doped titanium dioxide to an ethanol solution, adding 2% to 3% of the total weight of a dispersant, stirring for 30 to 40 minutes, and then ultrasonically dispersing for 8 to 10 minutes;
[0057] (2) adding fluorinated silane solution to the dispersion in a weight ratio of 1% to 2% of the nitrogen-doped titanium dioxide and stirring evenly;
[0058] (3) applying the composite coating evenly to the surface of the intermediate layer by spraying technology, with a thickness of 1-3 μm;
[0059] (4) The coated surface layer is cured under ultraviolet light with a wavelength of 365 nm for 10 minutes to form a surface structure with super hydrophobicity and photocatalytic properties.
[0060] Preferably, the cross-linking agent is isocyanate; the dispersant is polyvinyl pyrrolidone; and the volume ratio of ethanol to deionized water in the mixed solution of ethanol and deionized water is 3:1.
[0061] The present invention provides a self-cleaning nano coating material and a preparation process thereof. It has the following beneficial effects:
[0062] 1. The present invention uses nano-silicon dioxide, nano-alumina and graphene nanosheets as composite reinforcement materials, and uses silane coupling agent KH-550 to modify the surface of the particles, combines chemical vapor deposition (CVD) to prepare the bottom coating and spin coating technology to prepare the middle buffer layer, and significantly improves the mechanical strength and durability of the coating. Compared with the problem that the single-layer coating in the prior art is easily damaged by mechanical stress such as scratches and friction, the present invention solves the problem of failure of the coating caused by mechanical damage in actual use by enhancing the uniformity of particle dispersion and the division of labor and cooperation of the multi-layer structure, and greatly extends the service life of the coating.
[0063] 2. The present invention prepares nitrogen-doped titanium dioxide (N-TiO2) photocatalyst through nitrogen doping modification technology, so that it has high-efficiency photocatalytic performance under ultraviolet light and visible light, and combines the low surface energy fluorinated silane material on the surface of the coating to significantly improve the photocatalytic degradation ability and self-cleaning performance of the coating. Compared with the problem of coating dependence on ultraviolet light excitation and limited photocatalytic ability in the prior art, the present invention achieves efficient degradation of organic pollutants under natural light conditions through nitrogen-doped titanium dioxide with a wide spectrum response, solving the problem of insufficient self-cleaning ability of traditional coatings under weak light conditions.
[0064] 3. The present invention introduces a microcapsule repair system with epoxy resin as the repair agent and urea-formaldehyde resin as the capsule wall material. When the surface of the coating is partially damaged, the microcapsules rupture and release the repair agent for automatic repair, thereby restoring the structural integrity and performance of the coating. Compared with the problem in the prior art that the coating needs to be manually maintained or replaced once it is damaged, the present invention solves the problem of local failure of the coating in long-term use through the automatic repair function, which not only extends the service life of the coating, but also reduces the maintenance cost. It is particularly suitable for industrial and construction application scenarios with frequent wear.
[0065] 4. The present invention introduces fluorinated silane and nitrogen-doped titanium dioxide composite coating into the surface material, adopts a spraying process to prepare a surface coating with a thickness of 1-3 μm, and forms a super-hydrophobic surface with a micro-nano structure by ultraviolet light curing, with a surface contact angle of ≥150° and a rolling angle of ≤5°. Through layered coating and high-temperature post-treatment processes, the weather resistance and chemical stability of the coating under ultraviolet aging, acid-base environment and high humidity conditions are further enhanced. Compared with the problem of performance degradation of the coating due to aging or corrosion in the prior art, the present invention effectively solves the problem of unstable performance of the coating in harsh environments, so that it has the ability to maintain super-hydrophobic properties for a long time, and is particularly suitable for application scenarios such as architectural glass, solar panels and outdoor electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 This is a process flow chart for preparing self-cleaning nano-coating materials. DETAILED DESCRIPTION
[0067] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0068] Please see attached Figure 1 :
[0069] Example 1: Self-cleaning coating with enhanced mechanical strength and durability
[0070] Formula (by weight percentage):
[0071] Nano silicon dioxide (SiO2): 12%;
[0072] Nano-alumina (Al2O3): 6%;
[0073] Graphene nanosheets: 2%;
[0074] Nitrogen-doped titanium dioxide (N-TiO2): 10%;
[0075] Fluorinated silane (FAS-17): 3%;
[0076] Polyurethane (PU): 35%;
[0077] Polydimethylsiloxane (PDMS): 12%;
[0078] Microcapsule repair system: 5%;
[0079] Ethanol: 25%;
[0080] Deionized water: 8%.
[0081] Preparation process:
[0082] Substrate surface pretreatment:
[0083] The substrate was architectural glass, which was cleaned using isopropyl alcohol and deionized water (mixed in 1:1) and ultrasonically cleaned for 10 min;
[0084] Oxygen plasma etching (power 50 W, time 5 minutes) was performed to improve the surface activity, and the film was dried for 20 minutes.
[0085] Enhanced particle surface modification:
[0086] Mix nano-SiO2 and Al2O3 in a weight ratio of 2:1 and add them into the ethanol solution;
[0087] Add silane coupling agent KH-550 (2% of the total amount of particles) and stir for 60 minutes;
[0088] The modified particles were obtained by ultrasonic dispersion for 30 minutes, washing and drying for 12 hours.
[0089] Coating preparation:
[0090] Preparation of bottom layer: Modified SiO2, Al2O3 and graphene nanosheets were mixed in a ratio of 6:3:1, coated by chemical vapor deposition (CVD) technology with a thickness of 3 μm and cured at 120°C for 30 minutes;
[0091] Preparation of the middle layer: PU and PDMS were mixed and dissolved in a ratio of 3:1, and spin-coated on the bottom layer with a thickness of 8 μm and cured at 80°C for 15 minutes;
[0092] Surface preparation: nitrogen-doped N-TiO2 and fluorinated silane were mixed and sprayed in a ratio of 9:1, with a thickness of 2 μm, and cured by ultraviolet light (365 nm) for 10 minutes.
[0093] Post-processing:
[0094] Heat treatment at 150℃ for 12 minutes to improve interlayer bonding and overall durability.
[0095] Test results and analysis:
[0096] Mechanical properties: Taber wear test shows that the coating weight loss rate is less than 2% after 500 wears, and nanoindentation test shows that the surface hardness is increased by 50%.
[0097] Hydrophobicity: contact angle is 155 degrees, and sliding angle is less than 5 degrees.
[0098] Photocatalytic performance: The efficiency of methyl orange degradation under ultraviolet light is 90%, and the efficiency under visible light is 70%.
[0099] Summary of embodiments:
[0100] This embodiment introduces highly dispersible modified SiO2, Al2O3 and graphene composite particles, and combines them with a multilayer structure design to greatly improve the mechanical properties of the coating while maintaining good hydrophobicity and photocatalytic performance. Its photocatalytic efficiency is slightly lower than that of Example 2, but it meets the requirements for mechanical strength in high-frequency friction scenarios and is suitable for architectural glass and industrial equipment surfaces.
[0101] Example 2: Broad spectrum photocatalytic self-cleaning coating
[0102] Formula (by weight percentage):
[0103] Nano silicon dioxide: 11%;
[0104] Nano-alumina: 5%;
[0105] Graphene nanosheets: 1%;
[0106] Nitrogen-doped titanium dioxide: 12%;
[0107] Fluorinated silane: 4%;
[0108] Polyurethane: 32%;
[0109] Dimethicone: 10%;
[0110] Microcapsule repair system: 3%;
[0111] Ethanol: 28%;
[0112] Deionized water: 7%.
[0113] Preparation process:
[0114] Preparation of nitrogen-doped titanium dioxide:
[0115] Tetrabutyl titanate and urea were mixed in a molar ratio of 1:2 and the pH was adjusted to 4.5;
[0116] The nitrogen-doped primary product was obtained by hydrothermal reaction at 180 °C for 12 h;
[0117] The primary product was calcined at 450°C for 2 hours in a nitrogen atmosphere to obtain nitrogen-doped titanium dioxide.
[0118] Coating preparation:
[0119] Bottom layer: Nano-SiO2 and Al2O3 composite particles in a ratio of 4:1, coated by CVD technology, 4 microns thick, cured at 130°C for 20 minutes;
[0120] Middle layer: PU and PDMS solution spin-coated in a ratio of 3:1, thickness 6 μm, cured at 90°C for 15 minutes;
[0121] Surface layer: Spray nitrogen-doped N-TiO2 and fluorinated silane composite solution in a ratio of 8:2, with a thickness of 3 microns and UV curing for 12 minutes.
[0122] Test results and analysis:
[0123] Mechanical properties: Taber wear test shows that the coating weight loss rate is 3%, and the hardness is slightly lower than that of Example 1. Hydrophobicity: The contact angle is 150 degrees, and the rolling angle is less than 5 degrees.
[0124] Photocatalytic performance: The efficiency of methyl orange degradation under ultraviolet light is 96%, and the efficiency under visible light is 85%.
[0125] Summary of embodiments:
[0126] This embodiment improves the photocatalytic efficiency by optimizing the preparation process of nitrogen-doped TiO2, especially the degradation ability under visible light is significantly enhanced, but due to the low content of graphene and modified nanoparticles, the mechanical properties are slightly inferior to those of Example 1. This coating is suitable for solar panels and outdoor advertising screens that require high photocatalytic efficiency.
[0127] Example 3: Self-cleaning coating with self-repairing function
[0128] Formula (by weight percentage):
[0129] Nano silicon dioxide: 10%;
[0130] Nano-alumina: 6%;
[0131] Graphene nanosheets: 2%;
[0132] Nitrogen-doped titanium dioxide: 8%;
[0133] Fluorinated silane: 2%;
[0134] Polyurethane: 38%;
[0135] Dimethicone: 12%;
[0136] Microcapsule repair system: 6%;
[0137] Ethanol: 24%;
[0138] Deionized water: 7%.
[0139] Preparation process:
[0140] Microcapsule preparation:
[0141] Epoxy resin was used as a repair agent and urea-formaldehyde resin was used as a capsule wall material, and the capsule was prepared by emulsion polymerization.
[0142] The average particle size of the microcapsules is controlled at 3 microns.
[0143] Coating preparation:
[0144] Bottom layer: modified SiO2 / Al2O3 and graphene composite particles in a ratio of 6:3:1, CVD coating, thickness 3 microns, curing temperature 120°C, time 30 minutes;
[0145] Middle layer: PU and PDMS solution spin-coated in a ratio of 4:1, thickness 7 microns, curing temperature 90°C, time 15 minutes;
[0146] Surface layer: spraying of nitrogen-doped N-TiO2 and fluorinated silane solution, thickness 2 microns, UV curing for 10 minutes.
[0147] Test results and analysis:
[0148] Self-repairing ability: Scratch depth 10 microns, contact angle recovery rate after repair 85%;
[0149] Hydrophobicity: contact angle 152 degrees, sliding angle less than 5 degrees.
[0150] Photocatalytic performance: The degradation efficiency under UV light is 92%, and the efficiency under visible light is 72%.
[0151] Summary of embodiments:
[0152] This embodiment significantly improves the functional recovery ability of the coating by adding a microcapsule repair system, and is suitable for scenes with frequent mechanical wear. Its photocatalytic performance is lower than that of Example 2, but it has obvious self-repairing advantages and is suitable for automotive glass and high-end electronic equipment housings.
[0153] Example 4: Super hydrophobic weather-resistant self-cleaning coating
[0154] Formula (by weight percentage):
[0155] Nano silicon dioxide: 13%;
[0156] Nano-alumina: 6%;
[0157] Graphene nanosheets: 2%;
[0158] Nitrogen-doped titanium dioxide: 9%;
[0159] Fluorinated silane: 5%;
[0160] Polyurethane: 33%;
[0161] Dimethicone: 11%;
[0162] Microcapsule repair system: 4%;
[0163] Ethanol: 20%;
[0164] Deionized water: 10%.
[0165] Preparation process:
[0166] Coating preparation:
[0167] Bottom layer: SiO2 and Al2O3 composite particles in a ratio of 3:1, CVD coating, thickness 5 microns, cured at 140℃ for 20 minutes;
[0168] Middle layer: PU and PDMS solution spin-coated in a ratio of 3:1, thickness 6 μm, cured at 90°C for 15 minutes;
[0169] Surface layer: nitrogen-doped N-TiO2 and fluorinated silane spraying, thickness 2 microns, UV curing for 12 minutes.
[0170] Test results and analysis:
[0171] Weather resistance: After 500 hours of UV aging, the contact angle retention rate is 92%; there is no performance change after immersion in acid-base environment (pH2-12) for 24 hours;
[0172] Hydrophobicity: contact angle 153 degrees, sliding angle less than 5 degrees.
[0173] Photocatalytic performance: The degradation efficiency under UV light is 94%, and the efficiency under visible light is 78%.
[0174] Summary of embodiments:
[0175] This embodiment further enhances the hydrophobicity and optimizes the interlayer bonding force by increasing the fluorinated silane content, thereby improving weather resistance and environmental adaptability. It is suitable for outdoor architectural glass and solar panel applications.
[0176] Comparative experiment:
[0177] Experiment 1: Mechanical durability test
[0178] Purpose:
[0179] The mechanical strength and durability of the coatings under scratch and wear conditions were verified, demonstrating the improvement of mechanical properties by the coatings of the present invention.
[0180] Experimental process:
[0181] Sample preparation:
[0182] Prior art A: Pure polyurethane (PU, BASF brand Desmopan) commonly found on the market is used as the substrate, mixed with unmodified titanium dioxide (particle size 50 nanometers, Evonik P25), with titanium dioxide accounting for 10% by weight, and coated on the surface of the glass substrate using spin coating technology, with a coating thickness of about 5 microns, and cured at 80 degrees Celsius for 20 minutes.
[0183] Prior art B: Unmodified nano-silicon dioxide (particle size 20 nanometers, Evonik Aerosil 200) is dispersed in a polydimethylsiloxane (Dow Corning Sylgard 184) matrix at a mass fraction of 12%. The coating thickness after spin coating is about 6 microns and cured at 100 degrees Celsius for 20 minutes.
[0184] Example 1 of the present invention: A coating was prepared according to the formula of Example 1, the bottom layer contained modified nano silicon dioxide (10%) and aluminum oxide (5%), the surface layer contained nitrogen-doped titanium dioxide (10%), and the total thickness was 10 microns.
[0185] Example 4 of the present invention: A coating was prepared according to the formulation of Example 4, with the total content of the reinforcing particles further optimized to 18% and a thickness of 11 microns.
[0186] Experimental setup:
[0187] Wear test:
[0188] a. Installed on Taber abraser, using CS-10 grinding wheel, 500 g load, simulating 500 wear cycles.
[0189] b. Record the weight loss rate of the sample and observe the area of coating peeling.
[0190] Scratch test:
[0191] a. Use a nano scratch tester to apply different loads and record the scratch depth.
[0192] b. Use a microscope to photograph the scratch morphology.
[0193] Data collection:
[0194]
[0195] analyze:
[0196] The existing technologies A and B have limited mechanical properties, large scratch depth, and high weight loss rate after wear due to the single-layer structure and lack of modification mechanism. The present invention adopts a multi-layer composite structure, combined with surface modified reinforced particles, to effectively improve mechanical strength and durability.
[0197] Experiment 2: Photocatalytic performance test
[0198] Purpose:
[0199] The pollutant degradation capability of the coating under ultraviolet and visible light was verified, reflecting the wide spectrum response capability of the present invention.
[0200] Experimental process:
[0201] Sample preparation:
[0202] Prior art A: Undoped nano titanium dioxide (Evonik P25, particle size 50 nanometers) is dispersed in a BASF polyurethane (Desmopan) matrix at a mass fraction of 15%, and spin-coated to a thickness of about 4 micrometers and a curing temperature of 80 degrees Celsius.
[0203] Prior art B: silver-doped titanium dioxide (particle size 50 nanometers, purchased from Sigma-Aldrich) is mixed with Dow Corning Sylgard 184 at a mass fraction of 12%, and spin-coated to a thickness of about 5 micrometers and a curing temperature of 100 degrees Celsius.
[0204] Example 2 of the present invention: A coating was prepared according to the formula of Example 2, and the surface layer was nitrogen-doped titanium dioxide with a thickness of 10 microns.
[0205] Example 4 of the present invention: A coating was prepared according to the formula of Example 4, and the surface layer was nitrogen-doped titanium dioxide with a thickness of 11 microns.
[0206] Experimental setup:
[0207] Prepare 10 mg / L methyl orange solution (domestic analytical grade) and dispense equal amounts into four 250 ml beakers.
[0208] The samples were immersed in the solution and irradiated with ultraviolet light (365 nm) and visible light (420-750 nm) for 2 hours respectively.
[0209] The absorbance of the methyl orange solution was measured using a UV-visible spectrophotometer (PerkinElmer Lambda 365) to calculate the degradation efficiency.
[0210] Data collection:
[0211] sample UV degradation efficiency (%) Visible light degradation efficiency (%) Prior art A 72 15 Prior Art B 78 22 Embodiment 2 of the present invention 96 85 Embodiment 4 of the present invention 94 78
[0212] analyze:
[0213] The existing technology performs well under ultraviolet light conditions, but has low degradation efficiency under visible light. The coating of the present invention achieves a wide spectrum response through the design of nitrogen-doped titanium dioxide, especially the visible light degradation efficiency is nearly 4 times higher than that of the existing technology.
[0214] Experiment 3: Self-repair performance test
[0215] Purpose:
[0216] Verify the coating's ability to recover functionality after scratch damage.
[0217] Experimental process:
[0218] Sample preparation:
[0219] Prior art A and B: prepared according to the above-mentioned single-layer coating process, without introducing a repair function.
[0220] In Examples 3 and 4 of the present invention, epoxy resin (Sinopharm Group) was added to the coating as a repair agent, and urea-formaldehyde resin was used as a microcapsule wall material. The coating was prepared with the microcapsules accounting for 6% of the total weight of the coating, and the thickness was about 10 microns.
[0221] Experimental setup:
[0222] A nano scratch tester (Hysitron TI950) was used to scratch the coating surface with a depth of 10 μm.
[0223] After standing for 24 hours, the release of the repair agent was observed and the change in contact angle of the scratched area was measured.
[0224] Data collection:
[0225] sample Scratch depth (micrometer) Contact angle recovery rate (%) Prior art A 10 none Prior Art B 12 none Embodiment 3 of the present invention 10 85 Embodiment 4 of the present invention 10 80
[0226] In the prior art, the function is lost after scratching, but the coating of the present invention releases the repair agent through microcapsules, and the contact angle recovery rate reaches 80%-85%, indicating the remarkable effect of its self-repairing system.
[0227] Experiment 4: Hydrophobic performance stability test
[0228] Purpose:
[0229] Verify the coating's ability to maintain hydrophobic properties under UV aging and acid-base environments.
[0230] Experimental process:
[0231] Sample preparation:
[0232] Prior art A and B: prepared according to the above-mentioned single-layer coating process.
[0233] Embodiments 1 and 4 of the present invention: multi-layer composite coating, the surface layer contains fluorinated silane (Sigma brand), and the thickness is 10-11 microns.
[0234] Experimental setup:
[0235] UV aging experiment: The samples were exposed to 365 nm UV light for 500 hours.
[0236] Acid-base corrosion test: The samples were immersed in pH 2 and pH 12 solutions for 24 hours respectively.
[0237] The hydrophobicity was measured using a contact angle meter (KrüssDSA100).
[0238] Data collection:
[0239]
[0240] The existing coatings perform poorly in ultraviolet aging and acid-base corrosion environments. The coating of the present invention significantly improves the stability of hydrophobic performance through surface hydrophobic modified materials and multi-layer composite structures, and the contact angle retention rate reaches more than 95%.
[0241] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Self-cleaning nano coating material, characterized in that: The composition includes the following components, calculated by weight percentage: Nano silicon dioxide: 10%-15%, Nano-alumina: 5%-8%, Graphene nanosheets: 1%-3%, Nitrogen-doped titanium dioxide: 8%-12%, Fluorinated silane: 2%-5%, Polyurethane: 30%-40%, Polydimethylsiloxane: 10%-15%, Microcapsule repair system: 3%-6%, Ethanol: 20%-30%, Deionized water: 5%-10%.
2. The self-cleaning nano coating material according to claim 1, characterized in that: The nitrogen-doped titanium dioxide is subjected to nitrogen doping treatment at 400-500° C., specifically comprising the following steps: (1) mixing a titanium dioxide precursor and urea in a molar ratio of 1:2, wherein the titanium dioxide precursor is tetrabutyl titanate; (2) adding deionized water, adjusting the pH value of the solution to 4-5, and stirring to form a uniform solution; (3) subjecting the mixed solution to a hydrothermal reaction at 180° C. to 200° C. for 10 to 12 hours to obtain a nitrogen-doped titanium dioxide primary product; (4) The primary product is placed in a nitrogen atmosphere and calcined at 400-500° C. for 2 hours to obtain nitrogen-doped titanium dioxide with a wide spectrum response capability.
3. The self-cleaning nano coating material and its preparation process according to claim 1, characterized in that: The nano silicon dioxide and nano aluminum oxide in the reinforcing material are treated with a silane coupling agent KH-550 so that the particle surface has silicon oxygen functional groups, which specifically includes the following steps: (1) mixing nano-silicon dioxide and nano-aluminum oxide in a weight ratio of 2:1 and adding the mixture to a mixed solution of ethanol and deionized water; (2) adding KH-550 silane coupling agent to the solution, the amount of which is 2%-3% of the total weight of the particles; (3) stirring the mixture at room temperature for 50-60 minutes to allow the silane coupling agent to chemically adsorb on the surface of the particles; (4) After ultrasonic dispersion for 20-30 minutes, the mixture was washed with deionized water for three times, centrifuged, and finally dried at 60° C.-70° C. for 12 hours to obtain surface-modified nano-silicon dioxide and nano-aluminum oxide particles.
4. The preparation process of the self-cleaning nano coating material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Substrate surface pretreatment: Place the substrate in a solution of isopropanol and deionized water in a volume ratio of 1:1, ultrasonically clean for 10 minutes, rinse with deionized water and dry at 60°C for 20 minutes; etch the substrate surface with 50W oxygen plasma for 5 minutes; Enhanced particle surface modification: 15%-20% of the total weight of nano-silicon dioxide and nano-alumina are added to 100 mL of ethanol solution, and 2% of the total weight of the particles is added with silane coupling agent KH-550. After stirring for 60 minutes, ultrasonic dispersion is performed for 30 minutes, and then centrifugal separation and drying are performed to obtain modified particles. Dissolving the matrix material: dissolving polyurethane and polydimethylsiloxane in a mixed solution of ethanol and deionized water respectively, stirring for 60 minutes to form a uniform matrix solution; Introduction of functional additives: nitrogen-doped titanium dioxide and fluorinated silane were added to the matrix solution in proportion to the total weight of the coating, stirred for 30 minutes and ultrasonically dispersed for 10 minutes; Composite coating mixing: Add the modified particles and microcapsule repair system into the base solution and perform ultrasonic dispersion for 30 minutes to form a uniform coating; Multi-layer coating preparation: The bottom layer material is coated on the surface of the substrate by chemical vapor deposition technology with a thickness of 2-5 μm and cured at 120°C for 30 minutes; The intermediate layer material is coated on the bottom surface by spin coating technology at a rotation speed of 1000 rpm, with a thickness of 5-10 μm, and cured at 80° C.-100° C. for 10-20 minutes; The surface material is coated on the surface of the middle layer by spraying technology with a thickness of 1-3 μm, and cured by ultraviolet light with a wavelength of 365 nm for 10 minutes; Post-treatment: Use isocyanate treatment to enhance the interlayer bonding strength, and heat treat at 150℃-200℃ for 8-15 minutes.
5. The preparation process of the self-cleaning nano coating material according to claim 4, characterized in that: The microcapsule repair system is composed of epoxy resin as a repair agent and urea-formaldehyde resin as a capsule wall material. The particle size of the microcapsule is in the range of 2-5 μm.
6. The preparation process of the self-cleaning nano coating material according to claim 4, characterized in that: The bottom layer includes a composite coating of nano-silicon dioxide, nano-aluminum oxide and graphene nanosheets, and specifically includes the following steps: (1) mixing nano-silicon dioxide, nano-aluminum oxide and graphene nanosheets in a weight ratio of 6:3:1, adding the mixture to ethanol, and dispersing the mixture by ultrasonic for 60 minutes to form a uniform dispersion; (2) coating the dispersion on the surface of the substrate by chemical vapor deposition technology, adjusting the vapor pressure to 20-30 Pa and the reaction temperature to 300-400° C.; (3) The coating thickness is adjusted to 2-5 μm and cured at 120° C.-140° C. for 20-30 minutes to form a base structure.
7. The preparation process of the self-cleaning nano coating material according to claim 4, characterized in that: The intermediate layer includes a composite solution of polyurethane and polydimethylsiloxane, and specifically includes the following steps: (1) adding polyurethane and polydimethylsiloxane in a weight ratio of 3:1 into a mixed solution of ethanol and deionized water; (2) while stirring the solution to make it uniform, adding 0.5% to 1% by weight of a crosslinking agent, and continuing to stir for 60 minutes; (3) using a spin coating technique, coating the solution on the surface of the bottom layer at a rotation speed of 1000 rpm to form an intermediate layer with a thickness of 5-10 μm; (4) The coated intermediate layer is placed at 80°C-100°C for curing for 10-20 minutes.
8. The preparation process of the self-cleaning nano coating material according to claim 4, characterized in that: The surface layer includes a composite coating of nitrogen-doped titanium dioxide and fluorinated silane, and specifically includes the following steps: (1) adding nitrogen-doped titanium dioxide to an ethanol solution, adding 2% to 3% of the total weight of a dispersant, stirring for 30 to 40 minutes, and then ultrasonically dispersing for 8 to 10 minutes; (2) adding fluorinated silane solution to the dispersion in a weight ratio of 1% to 2% of the nitrogen-doped titanium dioxide and stirring evenly; (3) applying the composite coating evenly to the surface of the intermediate layer by spraying technology, with a thickness of 1-3 μm; (4) The coated surface layer is cured under ultraviolet light with a wavelength of 365 nm for 10 minutes to form a surface structure with super hydrophobicity and photocatalytic properties.
9. The preparation process of the self-cleaning nano coating material according to claim 8, characterized in that: The cross-linking agent is isocyanate; the dispersant is polyvinyl pyrrolidone; and the volume ratio of ethanol to deionized water in the mixed solution of ethanol and deionized water is 3:1.
Citation Information
Cited By
Macromolecule antiskid technology
CN120554936A
Liquid conveying pipeline capable of being shaped at will and forming method of liquid conveying pipeline
CN121316332A
Super-hydrophobic marine protective coating with sharkskin structure based on laser etching and method thereof
CN121555037A
Laser-etched sharkskin structure superhydrophobic marine protective coating and method thereof
CN121555037B
Anti-fingerprint coating for automobile touch screen as well as preparation method and application of anti-fingerprint coating
CN121592217A